Designing Geometry Teaching Materials Using Malay Batik Patterns on The Topic of Geometric Transformation - Roza, Yenita; Nurqolbi, Leliyana; Adnan, Arisman; Alawiyah, Tuti (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
Many mathematics books presented in an abstract way and ended in student's perception of difficult subject for mathematics. The goal of this research was to develop geometry learning instruction by using Malay batik patterns on the topic of transformation for junior high school students. The use of local context expect helping student in learning. The ADDIE model which consist of analysis, design, development, implementation, and evaluation is used in this RD research. A validation sheet serves as the validity instrument, which evaluates the accuracy of the instructional materials. The validity of teaching materials was determined with the average score was 3.57, which was considered to be valid. The practicality tool is a worksheet for utilising instructional resources. This study's implementation was carried out for a limited sample, the practicality percentage value is 89.61%, with a very practical category. The development of the research's end product has led to the creation of geometry transformation teaching materials for junior high school ninth graders that are both valid and practical and are based on Riau Malay batik themes.